Lessons Learned While Navigating the Academic Path in Human Factors. (September 2015) - Lum, Heather C.; Via, Christopher M.; Shelstad, William; Brill, J. Christopher; Bliss, James P.
The objective of this panel was to examine how individuals at different stages in their professional careers view human factors in relation to the educational process. The panel began by Heather Lum briefly giving an overview and the precipice for this discussion panel. The panelists then provided their views and experiences regarding this topic. William Shelstad discussed how he discovered human factors as an undergraduate and why he has chosen to pursue a path to graduate school. Christopher Via, a doctoral candidate, shared lessons he learned about being successful at that stage in his career. Chris Brill discussed his pursuits and the trials and tribulations of a tenure-track position in academia. Jim Bliss shared his experiences with the types of challenges faced by faculty in smaller universities. The specific theme of this discussion panel was focused on the differing perspectives that one might face as they move through the academic path of human factors. Each panelist had a unique perspective that was guided by where they are in the process and they shared these experiences as well as suggestions for those who are considering pursuing a similar path. Dr. Lum fostered discussion among the panelists and questions from the general audience. Discussion time: 90 minutes.